A Study on the Pollution Status of Akata Lake Sediments, Katsina-Ala Benue State, Nigeria - G.G, Yebpella; A.M, Magomya; B.N, Hikon; Y, Joshua; J, Gani (International Research Journal of Multidisciplinary Technovation, 2021)
Heavy metals accumulation in biological system are by inhalation of contaminated air, intake of contaminated food or drinking water has been considered to be an ecological menace to man and other organisms. This study was carried out to ascertain the pollution status of Cr, Pb, Zn, Cu and Cd in sediment of Akata Lake, Katsina- Ala Benue State, Nigeria. Sediment samples were collected, digested using 30% H2O2 followed by 0.5M HCl and the metal concentrations were determined with Varian AA240 Atomic absorption spectrophotometer equipped with Zeeman’s background correction (Varian, New Jersey, USA). The mean level of the heavy metals, Pb, Zn, Cu, Cd and Cr are 31.05, 2.72, 19.22 and 0.88 mg/kg while the concentration of Cr was below the detection limit of the instrument. The values obtained were compared with the established soil and sediment standard by World Health Organization (WHO). The contamination factors value for Zn, Cu and Cd are <1 while that of Pb is >1, hence it shows that the sediment is polluted by lead. The pollution load index (PLI) and Geo-accumulation index (Igeo) levels for Cr, Zn, Cu, Cd heavy metals in sample A - E were less than 1 except for Pb which is >1, this show that, the sediment were polluted with Pb.